2014
DOI: 10.1093/trstmh/tru030
|View full text |Cite
|
Sign up to set email alerts
|

Association of human leukocyte antigen class II allele and haplotypes in chikungunya viral infection in a western Indian population

Abstract: Association of HLA-DRB1*11 and the emergence of DRB1*11/DQB1*03 & DRB1*04/DQB1*03 as resistant and susceptible haplotypes towards CHIKV infection is being reported for the first time. Our results suggest that genetic susceptibility and/or resistance to chikungunya infection may be modulated by HLA class II alleles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Similarly, haplotypes DRB1*04, DRB1*03, DRB1*08, DRB1*09 and DRB1*11 are abundant in our class II specific epitopes. These haplotypes were seen to be associated with zoonotic viral infection [80, 81]. …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, haplotypes DRB1*04, DRB1*03, DRB1*08, DRB1*09 and DRB1*11 are abundant in our class II specific epitopes. These haplotypes were seen to be associated with zoonotic viral infection [80, 81]. …”
Section: Discussionmentioning
confidence: 99%
“…The DRB1 * 07 allele is associated with protection against Dengue virus infection in the Cuban population, but not in the Sri Lankan population ( 79 , 80 ). Studies have demonstrated HLA class II alleles association to susceptibility or resistance to CHIKV ( Table 1 , Figure 2 ), however none have reported associations with clinical symptoms of CHIKV infection ( 78 , 81 , 82 ).…”
Section: Host Genetics and Chikungunyamentioning
confidence: 99%
“…In India, two studies have reported the association of HLA alleles with CHIKV infection ( 78 , 81 ). One study demonstrated the presence of HLA-DRB1 * 04-HLA-DQB1 * 03 haplotype with susceptibility to CHIKV infection, and the presence of HLA-DRB1 * 11 and HLA-DRB1 * 11-HLA-DQB1 * 03 haplotype with resistance to the infection ( 81 ).…”
Section: Host Genetics and Chikungunyamentioning
confidence: 99%
See 1 more Smart Citation
“…These polymorphisms allow the immune system to increase the repertoire of peptides presented by HLA molecules, which in turn will affect the host's susceptibility to infectious diseases. There is evidence that HLA class II alleles are associated with susceptibility or resistance to CHIKV; however, no association has been reported with clinical symptoms of CHIKV infection (Bouquillard & Combe, 2009; Chaaithanya et al., 2013; Thanapati et al., 2014). There is a lack of evidence of association studies of HLA class I and II alleles in the Latin American CHIKV epidemic.…”
Section: Introductionmentioning
confidence: 99%